A Facile Synthesis, Characterization, and Photocatalytic Activity of Magnesium Ferrite Nanoparticles via the Solution Combustion Method - Loan T. T. Nguyen; Lan T. H. Nguyen; Nhuong Chu Manh; Dung Nguyen Quoc; Hai Nguyen Quang; Hang T. T. Nguyen; Duy Chinh Nguyen; Long Giang Bach (Journal of Chemistry)
In this study, we adopted the solution combustion method to synthesize magnesium ferrite (MgFe2O4) using urea as the fuel. Various techniques including TGA, XRD, SEM, TEM, FTIR, UV-Vis DRS, and EDS were employed to characterize the synthesized MgFe2O4 nanoparticles. The XRD analysis revealed that single-phase MgFe2O4 was formed at a calcination temperature of at 500–600°C for 3 hours in the absence of an intermediate phase. TEM analysis also revealed the formation of monodisperse magnesium ferrite nanoparticles, averaged at 30 nm in size. The photocatalytic activity of the synthesized MgFe2O4 nanoparticles against methylene blue dye under visible light was investigated, showing the efficiency of 89.73% after 240 minutes of light irradiation with the presence of H2O2.